A multiple timepoint pre-post evaluation of a ‘sexual respect’ dvd to improve competence in discussing sex with patients with disability - Dyer, Kerry; Aubeeluck, Aimee; Yates, Nicola L.; das Nair, Roshan (Springer Verlag, 2015)
Sexual problems are common after chronic illnesses and disability, yet research indicates that this is a neglected area in healthcare services. Evaluation studies provide evidence of the effectiveness of education in enhancing professionals’ knowledge, skills, and comfort in addressing patients’ sexual concerns. However, there are limited evaluations aimed at improving ability to discuss sexuality when working with people with disabilities. The overall aim of this study was to evaluate a ‘Sexual Respect’ DVD as an intervention to improve competence in addressing ‘sexuality and disability’. A mixed methods design was used with both quantitative and qualitative components. Nursing students’ self-report ratings of knowledge, confidence, comfort and willingness (to discuss sexuality) levels were collected across four time points: baseline, pre-intervention, post-intervention, and follow-up. Data were analysed using one-way repeated measures ANOVAs with post hoc comparisons. Open-ended qualitative comments relating to the barriers and facilitators to discussing sexuality were analysed using content analysis and subsequent frequency analysis. Reported barriers included lack of knowledge about sex¬uality and disability issues, the patient’s level of disability, and waiting for the patient to raise sexuality issues first. Facilitators included education/training, written information, and if the patient raised it first. Overall, the DVD intervention had a significant and positive impact on nursing students’ self-reported knowledge, confidence, comfort and willingness levels. The findings are discussed in relation to the PLISSIT model, which emphasises the importance of a proactive approach to addressing sexuality issues.